Measurements of sap flow for apple trees in relation to climatic and watering conditions - Nasr Z.; Ben Mechlia N. (Water saving in Mediterranean agriculture and future research needs [Vol. 1], 2007)
An experiment was conducted in a commercial apple orchard located near Tunis in order to determine the daily rates of sap flow of trees subjected to different watering conditions. The Golden Delicious cultivar planted on rows oriented NW/SE at a density of 1250 trees/hectare was used. Measurements included microclimatic factors and sap flow of two trees. Hourly data showed certain sensitivity to the existing natural thermal gradient in the morning. In spite of these discrepancies, it was possible to observe similarities between the daily course of sap flow and solar radiation although sap flow remained more or less constant when radiation reached a threshold value of about 500 w.m-2. However daily values were poorly correlated with radiation, vapour pressure deficit and temperature. These measurements were used to obtain a quantitative approximation of the basal crop coefficient (Kcb) over the entire growing season. Kcb increased from 0.4 at flowering to reach a plateau 60 days later at cell division stage. It remained thereafter constant at 0.75 for more than 60 days before decreasing to 0.5 at ripening. For the tree conducted under deficit irrigation, sap flow rates decreased by 35 percent in comparison to the fully irrigated one. Such decrease occurred at the end of the season when water supply covered 0.81 and 0.46 ETo for full and deficit irrigation trees respectively.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)